Effects of irrigation regimes on soil NO3–N, electrical conductivity and crop yield in plastic greenhouse - Chang, Tingting; Zhang, Yujie; Zhang, Zhanyu; Shao, Xiaoshou; Wang, Weina; Zhang, Jie; Yang, Xu; Xu, Huilian (International Journal of Agricultural and Biological Engineering, 2019)
Developing water-saving irrigation regimes has important practical significance not only in alleviating the crucial water shortage, but also in controlling soil salinization for the protected cultivation in eastern China. A field study with six treatments was conducted to evaluate the effects of different irrigation regimes with subdrainage systems on the soil nitrate nitrogen, salinity and moisture, also evaluate the effects on tomato growth, fruit yield and irrigation water use efficiency (IWUE). The treatments were distinguished by three different irrigation amounts of 310 mm, 360 mm and 410 mm, and two irrigation frequencies of 7 and 11 times. Results showed that the irrigation amount had significant effects on the soil NO3–N and electric conductivity (EC). A positive correlation was detected between soil NO3–N (x) and EC (y) at 0-20 m depth after harvest, with a linear equation of y = 0.063x – 0.670. Soil volumetric moisture at 0.10 m and 0.20 m depth was increased as the irrigation amount increased. Moreover, a higher amount of irrigation increased the fruit yield but reduced the IWUE of tomato. It was also found that smaller irrigation amounts combined with frequent intervals could increase fruit yield and IWUE. However, the fruit quality of tomato had a significant (p<0.05) negative correlation with irrigation amount. Therefore, the parameters of irrigation regime including the irrigation amount and intervals should be considered comprehensively in order to find a compromise between salinity control and irrigation water use efficiency improvement. Keywords: irrigation regimes, greenhouse, tomato, soil nitrate nitrogen, soil electric conductivity, soil salinity, water use efficiency DOI: 10.25165/j.ijabe.20191201.3022 Citation: Chang T T, Zhang Y J, Zhang Z Y, Shao X H, Wang W N, Zhang J, et al. Effects of irrigation regimes on soil NO3–N, electrical conductivity and crop yield in plastic greenhouse. Int J Agric & Biol Eng, 2019; 12(1): 109–115.